STABILITY INDICATING RP-LC ASSAY METHOD FOR CARISOPRODOL - Sangeetha, M.; ., Tirumala; ., Nagamallika (International Journal of Current Pharmaceutical Research, 2017)
Objective: A reverse phase stability-indicating HPLC method was developed for the determination of Carisoprodol in pharmaceutical dosage forms. The chromatographic elution was achieved on C18, 250 mm Ã— 4.6 mm, 5-Î¼m particle size column. Methods: The mobile phase contains a mixture of water and acetonitrile in ratio of 60:40 v/v. The flow rate was 1.0 ml min-1 and was detected by Refractive index detector. Results: The method was proven to be linear over a range of 1 to 4 mg/ml with a mean correlation coefficient of 0.99998. The %mean recovery is in the range of 100.55% to 101.11% and %RSD was less than 1.0% between preparations. The % RSD for Assay results of initial sample preparation in different intervals of 0hr, 24 h, 30 h and 48 h was less than 1.0%. To establish stability-indicating capability of the method, drug product was subjected to the stress conditions of acid, base, oxidative, hydrolytic, thermal and photolytic degradation. The degradation products were well resolved from Carisoprodol. Conclusion: The developed method was validated as per international ICH guidelines with respect to specificity, linearity, accuracy, precision and robustness.